(untitled) (Yearbook - Faculty of Economics, 2018)
In recent years in Macedonia there is significant migration of health workers, both within the country and abroad.For this purpose was conducted theoretical and empirical research and analyzed the attitudes and knowledge of health workers and managers or heads of departments in the public and private sector in the health system of the country. According to the obtained data,positive and negative consequences of migration in the health system of the Republic Macedonia have been identified, as well as managing the health workforce in order to prevent migration and rulemaking the health structure and organization of the health system. It was concluded that the policy makers need to plan the required number of doctors per capita of the number of health institutions in the country, to provide appropriate working conditions, career advancement and financial benefit because no-planned and unmanaged outflow of health workers which is in a steady rise can damage and so weakened health system of the country.